Conjugation-length dependence of regioregular oligo 3-alkyl(thienylene-vinylene)s demonstrates polyene-like behaviour with weak electron–electron correlations. Issue 16 (11th April 2023) - Polak, Daniel W.; Andrews, Iain; Farrow, George; Musser, Andrew J.; Auty, Alex; Chekulaev, Dimitri; Weinstein, Julia A.; Heeney, Martin; Clark, Jenny
Abstract : A time-resolved spectroscopic study of 3-alkyl(thienylene-vinylene) oligomers which sheds light on their photophysical behaviour, assigning them to be a polyene-like system. Abstract : Poly(3-alkyl(thienylene-vinylene)) (P3TV) and its longer oligomers have negligibly low photoluminescence quantum yields, however, the reason for their low yields is currently debated. Here, we prepare a series of regioregular (3-dodecyl)thienylene-vinylene oligomers with n = 2–8 repeat units by iterative Horner–Wadsworth–Emmons reactions, and report their steady-state, transient absorption, and emission spectroscopy. The results presented here demonstrate that 3-alkyl(thienylene-vinylene) oligomers form part of the polyene family. The shortest ( n = 2) oligomer emits from the bright 1Bu state, while fluorescence in oligomers with n = 3, 4 is from the formally dark 2Ag state, allowed via Herzberg–Teller vibronic coupling to the nearby bright 1Bu state as described for diphenyl-polyenes. Longer oligomers and the polymer are essentially non-emissive as the 2Ag state can no longer intensity-borrow from the 1Bu state. We demonstrate that the spectral shapes, photoluminescence quantum yield, and transient spectral behaviour can all be explained using a polyene model with weak electronic correlations.